PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK (PMR) TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VIII SMP NEGERI 42 PADANG - Nurhasanah, Nurhasanah; Suherman, Suherman (Jurnal Edukasi dan Penelitian Matematika, 2024)
Students' academic growth depends on math. Math achievement at SMP Negeri 42 Padang is subpar for grade VIII pupils. Thus, PMR is used to boost pupils' math skills. This study compares math achievement in PMR and standard learning approaches. This research will also show PMR-based pupils' math learning outcomes. Quasi Experiment with nonequivalent post-test only control group design underpins this work. Despite the reduction in the fifth meeting, the average student quiz results remained consistent at 70-80 grades, showing that experimental class students' mathematics learning outcomes increased overall. The research shows that PMR-based education improves math learning outcomes compared to standard teaching techniques in research.Keywords– Learning outcomes, Realistic Mathematics Education